Formative Assessment in Language Evaluation Class - Basori Basori; Harir Mubarok (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2020)
This study is intended to analyze variations of formative assessment strategies applied in Language Evaluation class. The class was taught by an English native speaker. A descriptive qualitative method was employed in the study in which interviews and classroom observations were conducted to collect the data. In addition, syllabus and materials used for the class were also used as the supporting instruments in the study. The findings set out that various kinds of formative assessment used in the respective class. They were oral question, choral questioning, a quiz, Think-Pair-Share, Think-Pair-Write-Share, pair work and group work. The delivery of each assessment technique are differed in each lesson, but are always preceded with questions before a specific technique used. The study advocates that formative assessment in higher education is highly suggested, yet real challenges lie for lecturers to apply.